Negative thermal expansion material, method for manufacturing the same, and paste

JP7939798B2Active Publication Date: 2026-10-22NIPPON CHEMICAL IND CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2022116580
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-07
Filing Date
2022-07-21
Publication Date
2026-10-22
Estimated Expiration
2042-07-21

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、溶媒としてプロピレンカーボネートを用いた場合において、適度な粘度を有するペーストが得られるリン酸タングステン酸ジルコニウムを含む負熱膨張材を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939798000001
    Figure 0007939798000001
  • Figure 0007939798000002
    Figure 0007939798000002
  • Figure 0007939798000003
    Figure 0007939798000003
Patent Text Reader

Abstract

To provide a negative thermal expansion material containing zirconium tungstate phosphate that provides a paste with a moderate viscosity when propylene carbonate is used as a solvent.SOLUTION: A negative thermal expansion material comprises at least surface-modified zirconium tungstate phosphate particles composed of zirconium tungstate phosphate particles and hydrogen peroxide present on the particle surface of the zirconium tungstate phosphate particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a negative thermal expansion material having the property of contracting in response to a rise in temperature, a method for producing the same, and a paste containing the negative thermal expansion material. [Background technology]

[0002] Many materials expand in length and volume due to thermal expansion when their temperature rises. In contrast, there are also materials that exhibit negative thermal expansion, where their volume decreases when heated (hereinafter sometimes referred to as "negative thermal expansion materials"). It is known that materials exhibiting negative thermal expansion can be used in combination with other materials to suppress changes in the thermal expansion of the material due to temperature changes.

[0003] Examples of materials exhibiting negative thermal expansion include β-eucryptite, zirconium tungstate (ZrW2O8), zirconium tungstate phosphate (Zr2WO4(PO4)2), and Zn. x CD 1-x (CN)2, manganese nitride, bismuth nickel iron oxide, etc. are known examples.

[0004] The linear thermal expansion coefficient of zirconium tungstate is -3.4 to -3.0 ppm / K in the temperature range of 0 to 400°C, and it exhibits large negative thermal expansion. By using it in combination with materials that exhibit positive thermal expansion (hereinafter sometimes referred to as "positive thermal expansion materials"), it is possible to manufacture materials with low thermal expansion (see, for example, Patent Documents 1 to 2).

[0005] The present inventors also previously proposed zirconium tungsdate phosphate, which is useful as a negative thermal expansion material (Patent Documents 3-4).

[0006] Pastes containing negative thermal expansion materials, as well as binder resins and flux materials such as low-melting-point glass, have been proposed for use as sealing and encapsulating materials for electronic devices such as FPDs (flat panel displays) including OLEDs, FEDs, PDPs, and LCDs, lighting devices using light-emitting elements such as OLEDs, solar cells such as dye-sensitized solar cells, packages for electronic components such as MEMS (Micro Electro Mechanical Systems) and optical devices, lighting bulbs, and glass components such as double-glazed glass.

[0007] Propylene carbonate and the like are often used as solvents for pastes of sealing and encapsulating materials (see, for example, Patent Documents 5-7). [Prior art documents] [Patent Documents]

[0008] [Patent Document 1] Japanese Patent Publication No. 2005-35840 [Patent Document 2] Japanese Patent Publication No. 2015-10006 [Patent Document 3] Japanese Patent Publication No. 2020-2000 [Patent Document 4] Patent No. 6105140 [Patent Document 5] Japanese Patent Publication No. 2019-94250, paragraph 0050 [Patent Document 6] Japanese Patent Publication No. 2021-35895, paragraph 0054 [Patent Document 7] Japanese Patent Publication No. 2018-90434, paragraph 0067 [Overview of the Initiative] [Problems that the invention aims to solve]

[0009] However, in the preparation of sealing materials using zirconium tungstate phosphate as a negative thermal expansion agent, there is a problem in that the viscosity of the paste tends to be low when propylene carbonate is used as a solvent, making it difficult to obtain a paste with a suitable viscosity. Furthermore, the binder resin, solvent, or positive thermal expansion agent mixed with the negative thermal expansion agent has various properties, and there is a demand for the development of negative thermal expansion agents containing zirconium tungstate phosphate with various surface properties suited to these properties.

[0010] Therefore, an object of the present invention is to provide a negative thermal expansion material containing zirconium tungstate phosphate that yields a paste with appropriate viscosity when propylene carbonate is used as the solvent. [Means for solving the problem]

[0011] In view of the above circumstances, the present inventors conducted extensive research and found that (1) surface-modified zirconium tungstate phosphate particles, in which hydrogen peroxide is stably present on the particle surface, can be obtained by contacting zirconium tungstate phosphate particles with hydrogen peroxide and phosphorus oxoacid; (2) the presence of hydrogen peroxide on the particle surface reduces the affinity between the particle surface of the surface-modified zirconium tungstate phosphate particles and propylene carbonate; and (3) a paste with high viscosity can be obtained by dispersing surface-modified zirconium tungstate phosphate particles, which have low affinity with propylene carbonate, in propylene carbonate. Based on these findings, the present invention was completed.

[0012] In other words, the first invention provided by the present invention is a negative thermal expansion material characterized by containing surface-modified zirconium tungstate phosphate particles, which consist of at least zirconium tungstate phosphate particles and hydrogen peroxide present on the particle surface of the zirconium tungstate phosphate particles.

[0013] Further, a second invention to be provided by the present invention is a method for producing a negative thermal expansion material, comprising a contacting step of bringing zirconium tungstate phosphate particles into contact with hydrogen peroxide and an oxoacid of phosphorus to obtain surface-modified zirconium tungstate phosphate particles.

[0014] Further, a third invention provided by the present invention is a paste comprising the negative thermal expansion material according to the first invention. Effects of the Invention

[0015] According to the present invention, it is possible to provide a negative thermal expansion material containing zirconium tungstate phosphate, which can yield a paste having an appropriate viscosity when propylene carbonate is used as a solvent. Modes for Carrying Out the Invention

[0016] Hereinafter, the present invention will be described based on preferred embodiments thereof. The negative thermal expansion material of the present invention is a negative thermal expansion material characterized by comprising surface-modified zirconium tungstate phosphate particles composed of at least zirconium tungstate phosphate particles and hydrogen peroxide present on the particle surfaces of the zirconium tungstate phosphate particles. That is, the negative thermal expansion material of the present invention includes surface-modified zirconium tungstate phosphate particles, and the surface-modified zirconium tungstate phosphate particles are composed of at least zirconium tungstate phosphate particles and hydrogen peroxide.

[0017] The zirconium tungstate phosphate particles according to the negative thermal expansion material of the present invention are particles whose particle surfaces are modified by allowing hydrogen peroxide and an oxoacid of phosphorus to be present on the particle surfaces. That is, the zirconium tungstate phosphate particles according to the negative thermal expansion material of the present invention are raw material particles (hereinafter also referred to as raw material ZWP particles) that are brought into contact with hydrogen peroxide and an oxoacid of phosphorus.

[0018] The zirconium tungstate phosphate particles (raw material ZWP particles) related to the negative thermal expansion material of the present invention are granular zirconium tungstate phosphate. Zirconium tungstate phosphate is represented by the following general formula (1). Zr x (WO4) y (PO4) z (1) (In the formula, x is 1.7≦x≦2.3, preferably 1.8≦x≦2.2, y is 0.85≦y≦1.15, preferably 0.90≦y≦1.10, and z is 1.7≦z≦2.3, preferably 1.8≦z≦2.2.)

[0019] In order to improve dispersibility and filling characteristics, the raw material ZWP particles preferably contain elements other than P, W, Zr and O, which are the elements contained in the zirconium tungstate phosphate represented by the general formula (1) (hereinafter, these are also referred to as "subcomponent elements").

[0020] Examples of the subcomponent elements include alkali metal elements such as Li, Na and K, alkaline earth metal elements such as Mg, Ca, Sr and Ba, transition metal elements such as Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Y, Nb, Mo, Ag, Hf and Ta, rare earth elements such as La, Ce, Nd, Sm, Eu, Tb, Dy, Ho and Yb, other metal elements other than transition metals such as Al, Zn, Ga, Cd, In, Sn, Pb and Bi, metalloid elements such as B, Si, Ge, Sb and Te, non-metal elements such as S, and halogen elements such as F, Cl, Br and I. One or more of these elements may be contained in the raw material ZWP particles. From the viewpoint of further improving dispersibility and filling characteristics, the raw material ZWP particles preferably contain at least one subcomponent element selected from Mg, Al and V, and in addition to this, from the viewpoint of facilitating the suppression of the thermal expansion coefficient, it is more preferable that the raw material ZWP particles contain Mg and / or Al as subcomponent elements.

[0021] In order to obtain excellent negative thermal expansion properties and excellent dispersibility and packing characteristics, the content of minor elemental components in the raw material ZWP particles is preferably 0.1 to 3.0 mass%, and more preferably 0.2 to 2.0 mass%, relative to the raw material ZWP particles. If two or more minor elemental components are included, the content of the minor elemental components is calculated based on the total mass of the minor elemental components. The content of minor elemental components is measured, for example, using a measuring device such as an X-ray fluorescence analyzer, by methods such as the powder pressing method or the molten glass bead method.

[0022] When the raw material ZWP particles contain both Mg and Al as minor elemental components, the negative thermal expansion properties, as well as the dispersibility and packing characteristics in positive thermal expansion materials, can be further improved. Therefore, the Al content in the raw material ZWP particles is preferably 100 to 6000 ppm by mass, and more preferably 1000 to 5000 ppm by mass, relative to the raw material ZWP particles. Furthermore, the Mg content in the raw material ZWP particles is preferably 0.10 to 3.0% by mass, and more preferably 0.22 to 2.0% by mass, relative to the raw material ZWP particles, in order to have a practical coefficient of linear expansion and to further improve dispersibility and packing characteristics.

[0023] The raw material ZWP particles are obtained by reacting a zirconium source, a tungsten source, a phosphorus source, and, if necessary, a source of minor elemental components. The method for producing the raw material ZWP particles is not particularly limited, and for example, (i) a method of mixing zirconium phosphorus oxoate, tungsten oxide, and a reaction accelerator such as MgO in a wet ball mill, and then calcining the resulting mixture (see, for example, Japanese Patent Publication No. 2005-35840), (ii) a method of wet mixing a zirconium source such as zirconium chloride, a tungsten source such as ammonium tungstate, and a phosphorus source such as ammonium phosphorus oxoate, and then calcining the resulting mixture (see, for example, Japanese Patent Publication No. 2015-10006), (iii) a method of calcining a mixture containing zirconium oxide, tungsten oxide, and ammonium dihydrogen phosphorus oxoate (see, for example, Materials Research (See Bulletin, 44 (2009), pp. 2045-2049), (iv) a method of calcining a reaction precursor using a mixture of a tungsten compound, an amorphous compound containing phosphorus and zirconium, and a source of minor elemental components added as needed (see, for example, International Publication No. 2017 / 061402).

[0024] Furthermore, in terms of facilitating handling when using the negative thermal expansion material of the present invention as a filler for the positive thermal expansion material, the BET specific surface area of ​​the raw material ZWP particles is preferably 0.1 to 50 m². 2 / g, more preferably 0.1 to 20m 2 The ratio is / g, and the average particle size of the raw material ZWP particles is preferably 0.02 to 50 μm, and more preferably 0.5 to 30 μm. The average particle size of the raw material ZWP particles is determined by observing 100 arbitrary raw material ZWP particles using a scanning electron microscope, measuring the maximum length of each particle, and taking the arithmetic mean of these values ​​as the average particle size of the raw material ZWP particles. In this case, the maximum length refers to the longest length of the line segment that crosses the two-dimensional projection image of the particle.

[0025] The particle shape of the raw material ZWP particles is not particularly limited and may be spherical, granular, plate-like, flaky, whisker-like, rod-like, filament-like, irregular crushed stone-like with one or more ridges (hereinafter also referred to as "crushed"), or a combination thereof. However, the particle shape of the raw material ZWP particles is preferably spherical because it has good fluidity and makes it easy to uniformly mix and disperse in the positive thermal expansion material.

[0026] The negative thermal expansion material of the present invention contains surface-modified zirconium tungstate phosphate particles. In the surface-modified zirconium tungstate phosphate particles, hydrogen peroxide is present on the surface of the zirconium tungstate phosphate particles (the particles of the raw material ZWP particles).

[0027] In the negative thermal expansion material of the present invention, the amount of hydrogen peroxide present is 0.01 to 1.5 parts by mass, preferably 0.03 to 1.0 parts by mass, per 100.0 parts by mass of raw material ZWP. By having the amount of hydrogen peroxide present in the negative thermal expansion material of the present invention within the above range, the surface of the raw material ZWP particles is efficiently coated with hydrogen peroxide.

[0028] In the surface-modified zirconium tungstate phosphate particles of the present invention, it is preferable that the hydrogen peroxide present on the surface is detected using hydrogen peroxide test paper (Merck, product name Quantofix Peroxid 25) after being left at room temperature (25°C) in a sealed container for 20 days or more in the water elution test described later, and that the hydrogen peroxide contained in the filtrate after filtration is detected using hydrogen peroxide test paper. This is preferable from the viewpoint that hydrogen peroxide can be stably present on the particle surface and that the negative thermal expansion material has excellent storage stability.

[0029] Furthermore, in the negative thermal expansion material of the present invention, from the viewpoint of providing a negative thermal expansion material with excellent storage stability, it is preferable that the surface-modified zirconium tungstate phosphate particles have phosphorus oxoacid present together with hydrogen peroxide on the surface of the zirconium tungstate phosphate particles (particles of the raw material ZWP particles).

[0030] Phosphorus oxoacids refer to compounds having a structure in which a hydroxyl group (-OH) and an oxy group (=O) are bonded to a phosphorus atom. Examples of phosphorus oxoacids include phosphoric acid (H3PO4), phosphonic acid (H3PO3), phosphinic acid (H3PO2), pyrophosphate (H4P2O7), and polyphosphate. Of these, phosphoric acid is preferred as a phosphorus oxoacid because it is easy to handle and inexpensive to obtain.

[0031] In the negative thermal expansion material of the present invention, the amount of phosphorus oxoacid present is 0.005 to 2.0 parts by mass, preferably 0.02 to 1.8 parts by mass, per 100.0 parts by mass of raw material ZWP. By having the amount of phosphorus oxoacid present in the negative thermal expansion material of the present invention within the above range, the surface of the raw material ZWP particles is efficiently coated with phosphorus oxoacid.

[0032] The relative proportions of hydrogen peroxide and phosphorus oxoacid in the negative thermal expansion material of the present invention are 10.0 to 200.0 parts by mass, preferably 20.0 to 180.0 parts by mass, of phosphorus oxoacid per 100.0 parts by mass of hydrogen peroxide. Having the relative proportions of hydrogen peroxide and phosphorus oxoacid within the above range is preferable because it allows for the acquisition of a paste with a more desirable viscosity when propylene carbonate is used as the solvent for the paste containing the negative thermal expansion material.

[0033] Examples of surface-modified zirconium tungstate phosphate particles related to the negative thermal expansion material of the present invention include a contact product of zirconium tungstate phosphate particles (raw material ZWP particles) and hydrogen peroxide and phosphorus oxoacid.

[0034] The method for contacting the raw material ZWP particles with hydrogen peroxide and phosphorus oxoacid is not particularly limited, and examples include (a) separately preparing a solution containing hydrogen peroxide and a solution containing phosphorus oxoacid, and contacting each with the raw material ZWP particles, and (b) contacting the raw material ZWP particles with a solution containing hydrogen peroxide and phosphorus oxoacid.

[0035] The negative thermal expansion material of the present invention uses propylene carbonate as a dispersion medium, and the Rsp value calculated from the following formula (1) is preferably 0.15 or less, and particularly preferably 0.05 to 0.15. Having the Rsp value calculated from the following formula (1) within the above range makes it easier to achieve an appropriate viscosity in the paste in which the negative thermal expansion material is dispersed in propylene carbonate.

[0036] Calculation formula (1): Rsp = (Rav / Rb) - 1 (1) In equation (1), Rav is the reciprocal of the NMR relaxation time when pulsed NMR is performed with the negative thermal expansion agent dispersed in propylene carbonate. Rb is the reciprocal of the NMR relaxation time when pulsed NMR is performed with the negative thermal expansion agent not dispersed in propylene carbonate.

[0037] The Rsp value is known to be an indicator of affinity and wettability to the solvent used as the dispersion medium (see, for example, Japanese Patent Publication No. 2019-67590, WO2018 / 116890 pamphlet, WO2020 / 091000 pamphlet, etc.). A large Rsp value indicates high affinity and excellent wettability to the solvent used as the dispersion medium.

[0038] The raw material ZWP particles, when dispersed in propylene carbonate, have an Rsp value greater than 0.15, as calculated using formula (1) above. In contrast, the negative thermal expansion material of the present invention has a smaller Rsp than the raw material ZWP particles, so it is believed that a paste with appropriate viscosity can be obtained even when propylene carbonate is used as the solvent.

[0039] In the propylene carbonate dispersion viscosity test, the dispersion viscosity when the negative thermal expansion material of the present invention is mixed and dispersed in propylene carbonate is preferably 20 to 100 MPa·s, and particularly preferably 20 to 80 MPa·s. When the dispersion viscosity in the propylene carbonate dispersion test is within the above range, the paste containing the negative thermal expansion material has an appropriate viscosity. In this invention, the propylene carbonate dispersion viscosity test is performed by the following method: 20.0 g of the negative thermal expansion material of the present invention is added to 6.0 g of propylene carbonate, and the mixture is mixed for 10 minutes at a rotation speed of 2000 rpm using a mixer (e.g., Awatori Rentaro ARV-310, manufactured by Shinky Co., Ltd.) to disperse the negative thermal expansion material of the present invention in the propylene carbonate, and the viscosity of the resulting mixed dispersion is measured using a viscometer (e.g., tuning fork viscometer SV-10, manufactured by A&D Co., Ltd.).

[0040] In the water elution test, the hydrogen peroxide elution concentration of the negative thermal expansion material of the present invention is preferably 0.5 to 10 ppm by mass. When the hydrogen peroxide elution concentration in the water elution test is within the above range, the paste containing the negative thermal expansion material has an appropriate viscosity. In the present invention, the water elution test is performed by the following method: First, 4.0 g of the negative thermal expansion material of the present invention is added to 10.0 mL of pure water, stirred and mixed at room temperature (25°C) for 1 minute, and then allowed to stand at room temperature (25°C). Next, after 20 hours, the supernatant is filtered through a 0.5 μm diameter membrane filter, and the resulting filtrate is analyzed using hydrogen peroxide test paper (Merck, product name: Quantofix Peroxid 25) to measure the hydrogen peroxide concentration of the filtrate. The hydrogen peroxide concentration of the filtrate is evaluated by comparing it with a color chart that shows hydrogen peroxide concentrations at concentration intervals of 0.5 ppm by mass, 2 ppm by mass, 5 ppm by mass, 10 ppm by mass, and 25 ppm by mass.

[0041] In addition to hydrogen peroxide and phosphorus oxoacids, tungstic acid, phosphotungstic acid, and other substances may be adsorbed on the surface of surface-modified zirconium tungstate particles for the purpose of enhancing the modification effect.

[0042] The negative thermal expansion material of the present invention is mainly composed of zirconium tungstate particles and therefore possesses negative thermal expansion properties. Furthermore, in the negative thermal expansion material of the present invention, hydrogen peroxide and phosphorus oxoacids are chemically adsorbed onto the surface of the zirconium tungstate particles, thus modifying the particle surface state of the zirconium tungstate particles and reducing the affinity between the solvent, particularly propylene carbonate, and the particle surface of the zirconium tungstate particles. As a result, when the negative thermal expansion material of the present invention is mixed and dispersed in a solvent, particularly propylene carbonate, the viscosity of the resulting paste increases. Moreover, in the negative thermal expansion material of the present invention, hydrogen peroxide can stably exist on the surface of the zirconium tungstate particles due to the interaction between hydrogen peroxide, phosphorus oxoacids, and zirconium tungstate phosphate on the surface of the zirconium tungstate particles. Therefore, in the negative thermal expansion material of the present invention, the modified state of the particle surface of zirconium tungstate particles by hydrogen peroxide and phosphorus oxoacid is maintained.

[0043] Next, a method for producing the negative thermal expansion material of the present invention will be described. The present invention provides a method for producing a negative thermal expansion material, characterized by a contact step in which zirconium tungstate particles are contacted with hydrogen peroxide and phosphorus oxoacid to obtain surface-modified zirconium tungstate particles.

[0044] The contact step in the method for producing the negative thermal expansion material of the present invention is a step of contacting zirconium tungstate particles (raw material ZWP particles) with hydrogen peroxide and phosphorus oxoacid. The zirconium tungstate particles (raw material ZWP particles) and phosphorus oxoacid used in the contact step are the same as those used in the negative thermal expansion material of the present invention.

[0045] In the contact process, there are no particular limitations on the method of contacting the zirconium tungstate particles with hydrogen peroxide and phosphorus oxoacid. For example, (a) a method of separately preparing hydrogen peroxide solution and an aqueous solution of phosphorus oxoacid and contacting each with the raw material ZWP particles, or (b) a method of contacting the raw material ZWP particles with a solution containing hydrogen peroxide and phosphorus oxoacid. Of these, method (b) is preferred because it simplifies the process.

[0046] Method (a) includes (a1) first contacting raw material ZWP particles with a solution containing hydrogen peroxide, then recovering the contact material between the raw material ZWP particles and hydrogen peroxide, and then contacting the recovered contact material between the raw material ZWP particles and hydrogen peroxide with a solution containing phosphorus oxoacid, and (a2) first contacting raw material ZWP particles with a solution containing phosphorus oxoacid, then recovering the contact material between the raw material ZWP particles and phosphorus oxoacid, and then contacting the recovered contact material between the raw material ZWP particles and phosphorus oxoacid with a solution containing phosphorus oxoacid. (a3) A method of contacting a solution containing hydrogen peroxide; (a4) A method of first contacting a solution containing hydrogen peroxide with the raw material ZWP particles, and then, without recovering the contact material, contacting the contact material between the raw material ZWP particles and the hydrogen peroxide solution with a solution containing phosphorus oxoacid; and (a5) A method of first contacting a solution containing phosphorus oxoacid with the raw material ZWP particles, and then, without recovering the contact material, contacting the contact material between the raw material ZWP particles and the phosphorus oxoacid with a solution containing hydrogen peroxide.

[0047] The hydrogen peroxide and phosphorus oxoacids used in the contact process are not particularly limited, as long as they are industrially available. Furthermore, the hydrogen peroxide and phosphorus oxoacids may be used as aqueous solutions.

[0048] The solution containing hydrogen peroxide and phosphorus oxoacid according to method (b) is an aqueous solution obtained by dissolving hydrogen peroxide and phosphorus oxoacid in an aqueous solvent. The aqueous solvent may be water alone or a mixed solvent of water and a hydrophilic solvent.

[0049] The hydrogen peroxide content in the solution containing hydrogen peroxide and phosphorus oxoacid according to method (b) is preferably 10.0 to 50.0% by mass, and particularly preferably 20.0 to 40.0% by mass. Having the hydrogen peroxide content in the solution containing hydrogen peroxide and phosphorus oxoacid within the above range is preferable because it allows for good workability and efficient contact treatment.

[0050] The content of phosphorus oxoacid in the solution containing hydrogen peroxide and phosphorus oxoacid according to method (b) is preferably 1.0 to 40.0% by mass, and particularly preferably 5.0 to 30.0% by mass. Having the phosphorus oxoacid content in the solution containing hydrogen peroxide and phosphorus oxoacid within the above range is preferable because it allows for good workability and efficient contact treatment.

[0051] (b) The ratio of hydrogen peroxide to phosphorus oxoacid in the solution containing hydrogen peroxide and phosphorus oxoacid in the method is preferably 70.0 to 130.0 parts by mass, and particularly preferably 80.0 to 120.0 parts by mass, of hydrogen peroxide per 100.0 parts by mass of phosphorus oxoacid. Having the above-mentioned ratio of hydrogen peroxide to phosphorus oxoacid in the solution containing hydrogen peroxide and phosphorus oxoacid is preferable because it allows for good workability and efficient contact treatment.

[0052] In method (b), a method for contacting the raw material ZWP particles with a solution containing hydrogen peroxide and phosphorus oxoacid is, for example, a method of mixing the raw material ZWP particles with a solution containing hydrogen peroxide and phosphorus oxoacid.

[0053] In method (b), when the raw material ZWP particles are brought into contact with a solution containing hydrogen peroxide and phosphorus oxoacid, the ratio of raw material ZWP particles to hydrogen peroxide is preferably 0.01 to 1.5 parts by mass, and particularly preferably 0.03 to 1.0 parts by mass, of hydrogen peroxide per 100.0 parts by mass of raw material ZWP particles. By having the ratio of raw material ZWP particles to hydrogen peroxide within the above range, the surface of the raw material ZWP particles is efficiently coated with hydrogen peroxide. Note that in the above ratio of raw material ZWP particles to hydrogen peroxide, the amount of hydrogen peroxide refers to the amount of hydrogen peroxide itself, not the amount of hydrogen peroxide solution.

[0054] In method (b), when the raw material ZWP particles are brought into contact with a solution containing hydrogen peroxide and phosphorus oxoacid, the ratio of raw material ZWP particles to phosphorus oxoacid is preferably 0.005 to 2.0 parts by mass, and particularly preferably 0.02 to 1.8 parts by mass, of phosphorus oxoacid per 100.0 parts by mass of raw material ZWP particles. By having the ratio of raw material ZWP particles to phosphorus oxoacid within the above range, the surface of the raw material ZWP particles is efficiently coated with phosphorus oxoacid. Note that in the above ratio of raw material ZWP particles to hydrogen peroxide, the amount of phosphorus oxoacid refers to the amount of phosphorus oxoacid itself, not the amount of phosphorus oxoacid solution.

[0055] In method (b), it is preferable to mix a solution containing hydrogen peroxide and phosphorus oxoacid in an amount of preferably 0.01 to 2.5 parts by mass, and particularly preferably 0.01 to 2.0 parts by mass, with 100.0 parts by weight of raw material ZWP particles, as this allows for efficient contact treatment with good workability, and also eliminates the need for drying, allowing the treated material to be used directly as a negative thermal expansion material.

[0056] The solution containing hydrogen peroxide according to method (a) is an aqueous solution obtained by dissolving hydrogen peroxide in an aqueous solvent, and the solution containing phosphorus oxoacid is an aqueous solution obtained by dissolving phosphorus oxoacid in an aqueous solvent. The aqueous solvent may be water alone or a mixed solvent of water and a hydrophilic solvent.

[0057] The hydrogen peroxide content in the solution containing hydrogen peroxide according to method (a) is preferably 10.0 to 50.0% by mass, and particularly preferably 20.0 to 40.0% by mass. Having the hydrogen peroxide content in the solution containing hydrogen peroxide within the above range is preferable because it allows for good workability and efficient contact treatment.

[0058] The phosphorus oxoacid content in the solution containing phosphorus oxoacid according to method (a) is preferably 1.0 to 40.0% by mass, and particularly preferably 5.0 to 30.0% by mass. Having the phosphorus oxoacid content in the solution containing phosphorus oxoacid within the above range is preferable because it allows for good workability and efficient contact processing.

[0059] The ratio of hydrogen peroxide in the hydrogen peroxide-containing solution and phosphorus oxoacid in the phosphorus oxoacid-containing solution according to method (a) is preferably 70.0 to 130.0 parts by mass, and particularly preferably 80.0 to 120.0 parts by mass, of hydrogen peroxide per 100.0 parts by mass of phosphorus oxoacid. Having the ratio of hydrogen peroxide in the hydrogen peroxide-containing solution and phosphorus oxoacid in the phosphorus oxoacid-containing solution within the above range is preferable because it allows for good workability and efficient contact treatment.

[0060] In method (a), a method for contacting the raw material ZWP particles with a solution containing hydrogen peroxide or a solution containing phosphorus oxoacid is, for example, a method of mixing the raw material ZWP particles with a solution containing hydrogen peroxide or a solution containing phosphorus oxoacid.

[0061] In method (a), when the raw material ZWP particles are brought into contact with a solution containing hydrogen peroxide, the ratio of raw material ZWP particles to hydrogen peroxide is preferably 0.01 to 1.5 parts by mass, and particularly preferably 0.03 to 1.0 parts by mass, of hydrogen peroxide per 100.0 parts by mass of raw material ZWP particles. By having the ratio of raw material ZWP particles to hydrogen peroxide within the above range, the surface of the raw material ZWP particles is efficiently coated with hydrogen peroxide. Note that in the above ratio of raw material ZWP particles to hydrogen peroxide, the amount of hydrogen peroxide refers to the amount of hydrogen peroxide itself, not the amount of hydrogen peroxide solution.

[0062] In method (a), when the raw material ZWP particles are brought into contact with a solution containing phosphorus oxoacid, the ratio of raw material ZWP particles to phosphorus oxoacid is preferably 0.005 to 2.0 parts by mass, and particularly preferably 0.02 to 1.8 parts by mass, of phosphorus oxoacid per 100.0 parts by mass of raw material ZWP particles. By having the ratio of raw material ZWP particles to phosphorus oxoacid within the above range, the surface of the raw material ZWP particles is efficiently coated with phosphorus oxoacid. Note that in the above ratio of raw material ZWP particles to hydrogen peroxide, the amount of phosphorus oxoacid refers to the amount of phosphorus oxoacid itself, not the amount of phosphorus oxoacid solution.

[0063] In method (a), it is preferable to mix a solution containing hydrogen peroxide and a solution containing phosphorus oxoacid with 100.0 parts by weight of raw material ZWP particles, preferably in total, 0.05 to 5.0 parts by mass, and particularly preferably 0.1 to 4.5 parts by mass, as this allows for efficient contact treatment with good workability, and also eliminates the need for drying, allowing the treated material to be used directly as a negative thermal expansion material.

[0064] In methods (a) and (b), the contact between zirconium tungsdate particles and hydrogen peroxide and phosphorus oxoacid can be a powder, slurry, paste, or solid depending on the amount of solution added. Therefore, the mixing treatment for contacting zirconium tungsdate particles with hydrogen peroxide and phosphorus oxoacid can be carried out by appropriately selecting a conventional wet or dry mixing treatment depending on the properties of the resulting mixture.

[0065] There are no particular restrictions on the equipment used for wet mixing, as long as it can produce a homogeneous mixture (contact material). Examples include stirrers, agitators with stirring blades, three-roll mills, ball mills, disperser mills, homogenizers, vibratory mills, sand grind mills, attritors, and powerful agitators. Wet mixing is not limited to mixing by the mechanical means exemplified above.

[0066] When performing dry mixing, mechanical means are preferable in that they yield a homogeneous mixture. While there are no particular restrictions on the equipment used for dry mixing as long as it can produce a homogeneous mixture, examples include high-speed mixers, super mixers, turbosphere mixers, Eilich mixers, Henschel mixers, Nauter mixers, ribbon blenders, V-type mixers, conical blenders, jet mills, cosmo-mizers, paint shakers, bead mills, and ball mills. However, at the laboratory level, household mixers or manual mixing are sufficient.

[0067] In methods (a) and (b), the temperature at which the zirconium tungstate particles are brought into contact with hydrogen peroxide and phosphorus oxoacid is not particularly limited, but is often 10 to 50°C, preferably 20 to 40°C. In the case of method (a), the temperature at which the solution containing phosphorus oxoacid or the solution containing hydrogen peroxide is brought into contact with the raw material ZWP particles is indicated.

[0068] In methods (a) and (b), the time for contacting the zirconium tungstate particles with hydrogen peroxide and phosphorus oxoacid is not critical in this manufacturing method, and in many cases, a satisfactory negative thermal expansion material can be obtained in 10 minutes or more, preferably 15 to 60 minutes. In the case of method (a), the time refers to the time for contacting the raw material ZWP particles with a solution containing phosphorus oxoacid or a solution containing hydrogen peroxide, respectively.

[0069] In methods (a) and (b), when zirconium tungstate particles are brought into contact with hydrogen peroxide and phosphorus oxoacid, the solution containing hydrogen peroxide and / or phosphorus oxoacid may optionally contain tungstic acid, phosphotungstic acid, etc., to enhance the modification effect.

[0070] In this way, in the contact step, zirconium tungstate particles are brought into contact with hydrogen peroxide and phosphorus oxoacid to obtain surface-modified zirconium tungstate phosphate particles, which are the contact product of zirconium tungstate particles and hydrogen peroxide and phosphorus oxoacid.

[0071] In the method for producing the negative thermal expansion material of the present invention, within the suitable range of the amount of solution containing hydrogen peroxide and phosphorus oxoacid added, or within the suitable range of the amount of solution containing hydrogen peroxide and phosphorus oxoacid added, the amount of solution containing hydrogen peroxide and phosphorus oxoacid added is small relative to the raw material ZWP particles, or the amount of solution containing hydrogen peroxide and phosphorus oxoacid added is small. Therefore, the properties of the contact material obtained by contacting the raw material ZWP particles with method (a) or (b) basically maintain a powder state even without drying.

[0072] Therefore, in the method for producing the negative thermal expansion material of the present invention, after the contact step, a drying treatment may be performed as necessary. Furthermore, in the method for producing the negative thermal expansion material of the present invention, crushing, pulverization, classification, etc. may be performed as necessary. In addition, when performing a drying treatment, the entire amount of the contact product between the zirconium tungstate particles and hydrogen peroxide and phosphorus oxoacid may be dried as is.

[0073] Furthermore, in the method for producing a negative thermal expansion material of the present invention, a negative thermal expansion material is obtained by performing a contact process, or, if necessary after the contact process, by performing drying, crushing, pulverization, classification, etc.

[0074] When raw ZWP particles are exposed to hydrogen peroxide alone, the hydrogen peroxide on the particle surface decomposes over time after contact, making it difficult to modify the ZWP particle surface. In contrast, by exposing the raw ZWP particles to phosphorus oxoacid in addition to hydrogen peroxide, both hydrogen peroxide and phosphorus oxoacid remain stable on the ZWP particle surface and are chemically adsorbed onto the ZWP particle surface, thereby modifying the ZWP particle surface. As a result, even when propylene carbonate is used as the solvent, a paste with appropriate viscosity can be obtained.

[0075] The negative thermal expansion material of the present invention can be used in powder or paste form. When used as a paste, the negative thermal expansion material of the present invention can be suitably used in the form of a paste containing a solvent and, if necessary, a binder resin. In other words, the paste of the present invention is characterized by containing the negative thermal expansion material of the present invention.

[0076] Solvents commonly used in the art are used in the paste. Examples include N,N'-dimethylformamide, ethylene glycol, dimethyl sulfoxide, dimethyl carbonate, propylene carbonate, butyrolactone, caprolactone, N-methyl-2-pyrrolidone, butylcarbitol acetate, propylene glycol dicetate, α-terpineol, α-terpineol, γ-butyllactone, tetralin, ethyl acetate, isoamyl acetate, diethylene glycol monoethyl ether, diethylene glycol monoethyl ether acetate, benzyl alcohol, toluene, 3-methoxy-3-methylbutanol, triethylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monobutyl ether, tripropylene glycol monomethyl ether, and tripropylene glycol monobutyl ether, which may be used individually or in combination of two or more. Furthermore, even when using propylene carbonate as a solvent, a paste with appropriate viscosity can be obtained with the negative thermal expansion material of the present invention; therefore, propylene carbonate is preferably used as a solvent in the paste of the present invention.

[0077] Furthermore, the paste of the present invention may optionally contain a binder resin. Binder resins commonly used in the art can be used. Specifically, examples of binder resins include celluloses such as nitrocellulose, methylcellulose, ethylcellulose, carboxymethylcellulose, oxyethylcellulose, benzylcellulose, and propylcellulose; polyalkylene carbonates such as polyethylene carbonate and polypropylene carbonate; (meth)acrylic acid resins such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; polyethylene glycol derivatives; and polymethylstyrene. These may be used individually or in combination of two or more.

[0078] The content of the negative thermal expansion agent in the paste of the present invention is not particularly limited, but is often 1 to 99% by volume, and preferably 10 to 90% by volume.

[0079] A paste containing the negative thermal expansion material of the present invention, and further containing a fluxing material, is suitably used, for example, as a paste for sealing materials or a paste for encapsulating materials.

[0080] Examples of flux materials to be included in the paste of the present invention include low-melting-point glasses, and those commonly used in the art can be used. For example, PbO-B2O3 system, PbO-SiO2-B2O3 system, Bi2O3-B2O3 system, Bi2O3-SiO2-B2O3 system, SiO2-B2O3-Al2O3 system, SiO2-B2O3-BaO system, SiO2-B2O3-CaO system, ZnO-B2O3-Al2O3 system, ZnO-SiO2-B2O3 system, P2O5 system, SnO-P2O5 system, V2O5-P2O5 system, V2O5-Mo2O3 system, and V2O5-P2O5-TeO2, etc.

[0081] The content of the flac material in the paste of the present invention is not particularly limited, but is often 10 to 90% by volume, and preferably 15 to 90% by volume.

[0082] When used as a sealing material paste, it is preferable to prepare the paste with a blending ratio of flux and negative thermal expansion agent such that the flux accounts for 60-90% by volume and the negative thermal expansion agent of the present invention accounts for 10-40% by volume, with a binder resin of 0.1-40% by mass and a solvent of 5-40% by mass.

[0083] Furthermore, when used as a paste for sealing double-glazed glass, the sealing paste can be used with glass beads known in the art contained within it.

[0084] The paste of the present invention may optionally further contain additives known in the art, such as defoaming agents, dispersants, coloring pigments, and thixotropy-imparting agents.

[0085] Furthermore, the negative thermal expansion material of the present invention can also be used as a composite material by using the negative thermal expansion material as a powder and incorporating it into a positive thermal expansion material, and by adjusting the mixing ratio of the negative thermal expansion material, it can be used as a material with negative thermal expansion, zero thermal expansion, or low thermal expansion.

[0086] Examples of positive thermal expansion materials containing the negative thermal expansion material of the present invention include various organic compounds or inorganic compounds.

[0087] Examples of the aforementioned organic compounds include rubber, polyolefins, polycycloolefins, polystyrene, ABS, polyacrylate, polyphenylene sulfide, phenolic resins, polyamide resins, polyimide resins, epoxy resins, silicone resins, polycarbonate resins, polyethylene resins, polypropylene resins, polyethylene terephthalate resins (PET resins), and polyvinyl chloride resins.

[0088] Examples of the inorganic compounds include metals, alloys, silicon dioxide, graphite, sapphire, various types of glass, concrete materials, and various types of ceramic materials.

[0089] Of these, the positive thermal expansion material is preferably at least one selected from metals, alloys, glass, ceramics, rubber, and resins. In the composite material according to the present invention, the amount of negative thermal expansion material added can be a general amount in the art. [Examples]

[0090] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0091] (Preparation of raw material ZWP particles) Fifteen parts by mass of commercially available tungsten trioxide (WO3; average particle size 1.2 μm) were placed in a beaker, and then 84 parts by mass of pure water were added. The mixture was stirred at room temperature (25°C) for 120 minutes to prepare a 15 mass% slurry containing tungsten trioxide. The average particle diameter of the solid content in the slurry was 1.2 μm. Next, zirconium hydroxide, an 85 mass% phosphoric acid aqueous solution, and magnesium hydroxide were added to this slurry at room temperature (25°C) such that the molar ratio of Zr:W:P:Mg in the slurry was 2.00:1.00:2.00:0.10, then the temperature was raised to 80°C, and the reaction was carried out under stirring for 4 hours. After the reaction was completed, 1 part by mass of ammonium polycarboxylate as a dispersant was charged, and while stirring the slurry, the slurry was supplied to a media-agitation type bead mill charged with 0.5 mm diameter zirconia beads, mixed for 15 minutes, and subjected to wet grinding. The average particle diameter of the solid content in the slurry after wet grinding was 0.3 μm. Next, the slurry was supplied to a spray dryer set at 220°C at a supply rate of 2.4 L / h to obtain a reaction precursor. As a result of X-ray diffraction performed on the obtained reaction precursor, only the diffraction peak of tungsten trioxide was observed. Further, when analyzed by FT-IR, the range of 950 to 1150 cm -1 had an infrared absorption peak, and the maximum value of the infrared absorption peak in this range was at 1042 cm -1 appeared at this position. Next, the obtained reaction precursor was subjected to a calcination reaction in the air at 1050°C for 2 hours to obtain a white calcined product. When the obtained calcined product was analyzed by X-ray diffraction, the calcined product was single-phase Zr₂(WO₄)(PO₄)₂. This was designated as raw material ZWP particles.

[0092]

Table 1

[0093] (Preparation of a solution containing hydrogen peroxide and phosphoric acid) A 30.0 mass% hydrogen peroxide aqueous solution and an 85.0 mass% phosphoric acid aqueous solution were mixed at a weight ratio of 10:2 to prepare a solution containing hydrogen peroxide and phosphoric acid.

[0094] (Example 1) 100.0 g of the raw material ZWP particles prepared as described above were placed in a resealable plastic bag. Next, 0.40 g of the solution containing hydrogen peroxide and phosphorus oxoacid prepared as described above was added to it, and the mixture was manually mixed for 10 minutes at room temperature (25°C) to obtain a contact sample. This sample was left at room temperature (25°C) in a sealed container for 20 days and was used as the negative thermal expansion material sample.

[0095] (Example 2) 100.0 g of the raw material ZWP particles prepared as described above were placed in a resealable plastic bag. Next, 0.60 g of the solution containing hydrogen peroxide and phosphorus oxoacid prepared as described above was added to it, and the mixture was manually mixed for 10 minutes at room temperature (25°C) to obtain a contact sample. This sample was left at room temperature (25°C) in a sealed container for 20 days and was used as the negative thermal expansion material sample.

[0096] (Example 3) 100.0 g of the raw material ZWP particles prepared as described above were placed in a resealable plastic bag. Next, 0.80 g of the solution containing hydrogen peroxide and phosphorus oxoacid prepared as described above was added to it, and the mixture was manually mixed for 10 minutes at room temperature (25°C) to obtain a contact sample. This sample was left at room temperature (25°C) in a sealed container for 20 days and was used as the negative thermal expansion material sample.

[0097] (Comparative Example 1) The raw material ZWP particles prepared as described above were used as the negative thermal expansion material sample.

[0098] (Comparative Example 2) 100.0 g of the ZWP particles prepared as described above were placed in a resealable plastic bag. Next, 0.33 g of deionized water was added, and the mixture was manually mixed for 10 minutes at room temperature (25°C) to obtain a mixture, which was used as the negative thermal expansion material sample.

[0099] (Comparative Example 3) 100.0 g of the ZWP particles prepared as described above were placed in a resealable plastic bag. Next, 0.40 g of a 30.0% by mass hydrogen peroxide aqueous solution was added, and the mixture was manually mixed for 10 minutes at room temperature (25°C) to obtain a mixture. This mixture was left at room temperature (25°C) in a sealed container for 20 days to be used as a negative thermal expansion material sample.

[0100] [Table 2]

[0101] (Measurement of linear thermal expansion coefficient) <Fabrication of ceramic molded bodies> 0.5 g of the negative thermal expansion material sample obtained in the examples and comparative examples, and 0.05 g of the binder (SpectroBlend 44 μm Powder) were mixed in a mortar for 5 minutes, and the entire amount was filled into a 3 mm × 20 mm mold. Next, a powder molded body was produced by molding with a pressure of 2 tons using a hand press. The obtained powder molded body was fired in an electric furnace at 1100 °C for 2 hours in an air atmosphere to obtain a ceramic molded body of zirconium tungstate phosphate. <Measurement of thermal expansion coefficient> The linear thermal expansion coefficient of ceramic molded bodies was measured using a thermomechanical measuring device (NETZSCH JAPAN TMA4000SE). The measurement conditions were a nitrogen atmosphere, a load of 10g, and a temperature range of 50°C to 250°C.

[0102] (Measurement of Rsp values ​​using propylene carbonate as the dispersion medium) 1.0 g of the negative thermal expansion material sample was added to 20.0 ml of pyropylene carbonate and ultrasonically dispersed for 20 minutes (130 W) to obtain a dispersion. Next, the relaxation time at 25°C was measured using a pulsed NMR spectrometer (manufactured by Luft Corporation), and the Rsp value was calculated using the following formula (1). Rsp = (Rav / Rb) - 1 (1) In equation (1), Rav is the reciprocal of the NMR relaxation time when pulsed NMR is performed with 1.0 g of the negative thermal expansion material sample dispersed in 20.0 ml of propylene carbonate, and Rb is the reciprocal of the NMR relaxation time when pulsed NMR is performed with a blank of 20.0 ml of propylene carbonate without the negative thermal expansion material dispersed.

[0103] (Propylene carbonate dispersion viscosity test) 20.0 g of negative thermal expansion material sample and 6.0 g of propylene carbonate were weighed and mixed in a mixer (Thinky Co., Ltd., Awatori Rentaro ARV-310) at a rotation speed of 2000 rpm for 10 minutes to prepare a 30 Vol% mixed dispersion (paste). The viscosity of this mixed dispersion (paste) was measured using a tuning fork viscometer SV-10 (manufactured by A&D Company, Limited).

[0104] (Water elution test) 4.0 g of a negative thermal expansion material sample was added to 10.0 mL of pure water, stirred and mixed at room temperature (25°C) for 1 minute, and then allowed to stand at room temperature (25°C). After 20 hours, the supernatant was filtered through a 0.5 μm diameter membrane filter, and the hydrogen peroxide concentration of the resulting filtrate was analyzed using hydrogen peroxide test paper (Merck, product name: Quantofix Peroxid 25). The hydrogen peroxide concentration of the filtrate was determined by comparison with a color chart showing hydrogen peroxide concentrations at intervals of 0.5 ppm, 2 ppm, 5 ppm, 10 ppm, and 25 ppm.

[0105] [Table 3]

[0106] As is clear from Table 2, the negative thermal expansion material obtained in the examples yields a paste with appropriate viscosity when mixed and dispersed in propylene carbonate.

Claims

1. A negative thermal expansion material characterized by containing surface-modified zirconium tungstate phosphate particles, which consist of at least zirconium tungstate phosphate particles and hydrogen peroxide present on the particle surface of the zirconium tungstate phosphate particles.

2. The negative thermal expansion material according to claim 1, characterized in that the surface-modified zirconium tungstate phosphate particles are a contact product of zirconium tungstate phosphate particles, hydrogen peroxide, and phosphorus oxoacid.

3. The negative thermal expansion material according to claim 1, characterized in that the zirconium tungstate phosphate further contains minor component elements.

4. The negative thermal expansion material according to claim 3, characterized in that the aforementioned minor component elements are one or more selected from the metallic elements Mg, V, and Al.

5. The negative thermal expansion material according to claim 1, characterized in that the Rsp value obtained from the following calculation formula (1) using propylene carbonate as the dispersion medium is 0.15 or less. Rsp=(Rav / Rb)-1 (1) (In equation (1), Rav is the reciprocal of the NMR relaxation time when pulsed NMR is measured with a negative thermal expansion material dispersed in propylene carbonate. Rb is the reciprocal of the NMR relaxation time when pulsed NMR is measured with no negative thermal expansion material dispersed in propylene carbonate.)

6. A method for producing a negative thermal expansion material, characterized by having a contact step in which surface-modified zirconium tungstate phosphate particles are contacted with hydrogen peroxide and phosphorus oxoacid to obtain zirconium tungstate phosphate particles.

7. The method for producing a negative thermal expansion material according to claim 6, characterized in that the contact step is carried out by mixing the zirconium tungstate particles with a solution containing hydrogen peroxide and phosphorus oxoacid.

8. The method for producing a negative thermal expansion material according to claim 6 or 7, characterized in that the zirconium tungstate phosphate further contains minor component elements.

9. A paste characterized by containing the negative thermal expansion material described in claim 1 or 3.

Citation Information

Patent Citations

  • Fixing metal fittings of moisture-proof sheet

    JP1986005140A

  • Sealing material

    JP2005035840A

  • Negative-expansion ceramic

    JP2015010006A

  • Sealing material paste

    JP2018090434A

  • Negative electrode material for lithium ion secondary battery, negative electrode for lithium ion secondary battery, and lithium ion secondary battery

    JP2019067590A